Monetary dependence and official dollarization: the case of East Timor - Kuele, Giovanna (2016)
The paper investigates and analyzes the effects of monetary dependency through official dollarization of national economies. We proceeded to study the case of East Timor, which has a dollarized economy since 2000. The dollarization seemed to be resulting more in disadvantages than advantages at least for this case.